US farm support under a Biden administration: Plus ça change, plus c'est la même chose? - Glauber, Joseph W.; Smith, Vincent H. (Canadian Agricultural Economics Society, 2021)
During the Trump administration, there has been an unprecedented increase in the level of domestic support provided to US agricultural producers. Direct farm supports, including price and income support payments, federal crop insurance, and supplemental assistance to compensate losses due to the trade war with China and the pandemic, have accounted for more than one‐third of net farm income. Those payments have threatened to push the United States over its World Trade Organization (WTO) domestic support obligations and increased its vulnerability to potential dispute settlement challenges in the WTO. The incoming Biden administration will likely bring a new focus to repurpose farm subsidies to provide environmental benefits, such as reduced greenhouse gas emissions, but to achieve those reforms they will need to convince a US Congress that has historically been prone to maintaining the status quo.